Evaluation of Groundwater Quality Using Water Quality Index (WQI) in Ambedkar Nagar City, Uttar Pradesh, India - Dheeraj V.P.; Sonkar A.K.; Singh C.S. (My University, 2025)
The groundwater is an important natural resource utilized for drinking and many more purposes. The present study is aimed to assess the quality of groundwater using the water quality index (WQI) methods in Ambedkar Nagar district (U.P), India. A total of 10 groundwater samples were collected from ten different areas of Ambedkar Nagar district in November 2018, and samples were analyzed to investigate the suitability of groundwater for domestic purposes. The selection of locations for sampling has been based on a preliminary field survey. Ten groundwater samples were examined for physical and chemical parameters such as pH, electrical conductivity, total dissolved solids, calcium, sodium, magnesium, potassium, bicarbonates, sulfate, nitrate, fluoride, and chloride. The values have been computed and compared with the guideline values for drinking water given by the World Health Organization (WHO). It has been observed that the calculated WQI ranges from 31.2 to 64.3 which represents excellent to good and good to the poor category of groundwater quality of studied areas. The high value of WQI is due to higher concentrations of electrical conductivity (EC), bicarbonate (HCO3 −), and total dissolved solids (TDS) in the groundwater samples at some of the selected locations. The result shows that the groundwater at few locations required minor treatment before the consumption. © 2022, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.